Single and combined effects of Oil Palm’s empty fruit bunch compost and hexaconazole on the growth and yield of sandy soil grown sweet potato [Ipomoea batatas (L.) Lam.] var. VitAto / Borhan Abdul Haya @ Yahya - Abdul Haya @ Yahya, Borhan (2016)
The orange-fleshed sweet potato variety VitAto is one o f the important crops under the East Coast Economic Region (ECER). This crop has been selected to replace tobacco which was widely grown under Beach Ridges Interspersed with Swales (BRIS) soil in Kelantan and Terengganu. Federal Agricultural Marketing Authority (FAMA) is the government agency responsible for the marketing o f farmers’ agricultural produce. VitAto storage root is currently marketed based on sizes, grades A, B and C which represent big, medium and small respectively with bigger size generally fetching higher prices. Unfortunately, the storage root yield obtained by farmers generally consisted of high proportion o f grades B and C and only a few o f grade A. To overcome the problem o f low VitAto storage root yield obtained by farmers, the application o f empty fruit bunch (EFB) compost and hexaconazole (HEX) as a plant growth regulator were explored as treatments to increase yield. Field experiments were conducted for two seasons from October 2012 to June 2013. The effects o f these treatments were compared to existing recommended inorganic fertilization practice by examining the following aspects; growth, yield, nutrients and |3 carotene content. These experiments were laid in randomized complete block design (RCBD), replicated four times. Both the EFB and HEX treatments were carried out separately in two different experimental plots during the first season. In the EFB experiment, four treatments were used; control (current practice), EFB alone, a combination o f EFB and control with 2:1 ratio and a combination o f EFB and control with 1:2 ratio. All these treatments were applied at 7, 28 and 35 days after planting (DAP). The rates o f nitrogen (N), phosphorus (P) and potassium (K) in all treatments were synchronized before application. In the HEX experiment, five treatments o f various concentrations namely, 0, 10, 20, 30 and 40 ppm were used and given at 20, 40 and 60 DAP. Selected treatments that gave good positive results from both experiments were used in the subsequent third experiment conducted in the second season. This third experiment consisted o f four treatments namely; control (current practice), EFB alone and combination treatments o f EFB with 10 ppm HEX and the final treatment o f EFB with 30 ppm HEX. Combination treatment o f EFB with 30 ppm HEX application was shown to give positive results in most o f the parameters measured at the maturity stage. The storage root number, fresh weight, dry mass, 0- carotene content, K concentration and content were increased by 16.9%, 125%, 34.4%, 18.13%, 69.4% and 75.5% compared to control treatment respectively. Similarly, root to shoot ratio and harvest index were also increased by 15.2% and 58.80% respectively. The EFB compost increased the yield through greater K availability from the compost to plant. In contrast, HEX enhanced the translocation o f K into the storage root. The K nutrient enhanced the assimilate translocation from the source to sink organ primarily to storage root probably due to increased sink strength o f storage root to attract more assimilates. The high K uptake contributes to high assimilate accumulation in the storage root. The K nutrient also responsible for an increase in the storage root numbers which maximize the marketable storage root as well as storage root total fresh weight. The combination treatment between EFB compost with 30 ppm HEX could be used to substitute or as an alternative to the current practice o f the use o f inorganic fertilization in VitAto cultivation under BRIS soil.